Analisis Pengendalian Mutu Minyak Sawit Dengan Metode SQC Pada PKS PT. Perkebunan Nusantara IV Adolina - Sitinjak, Riva Suyanto; Banjarnahor, Marali; Delvika, Yuana (Universitas Medan Area, 2022)
PT. Perkebunan Nusantara IV Adolina North Sumatra is a company engaged in the processing of palm oil. The product produced is Crude Palm Oil (CPO). Quality control is the use of techniques and activities to achieve maintain and improve the quality of a product or service. While Statistic Quality Control is a statistical technique used widely to ensure that processes meet standards. This study aimed to analyze the quality control of palm oil if it meets the standard, and then do quality improvement so as not to vary too far from the standards that have been determined because the better quality is far from the limit control, the result obtained is better for the company to gain trust about the quality of CPO, an analysis was carried out by managing inspection data of seven quality parameters using control chart analysis tool and cause-effect diagrams. From the results of the research conducted, it was found that 3 parameters greatly affect the quality of palm oil, namely ALB content, moisture content, and dirt content. The cause of high ALB levels. Moisture content, and dirt content are due to improper maturity, storage duration, and not doing good sorting. In addition, the engine performance is unstable due to the age of the engine that has been operating for a long time.